Загадка «Олеговой могилы»: Киев или Ладога? - Рычка, В.М. (Археологія і давня історія України, 2020)
Статья посвящена проблеме локализации места погребения князя Олега Вещего, правившего в Киеве при Игоре Рюриковиче в 882—912 гг. Described in Primary Chronicle under 912 the story of the unusual circumstances of the death of Kyiv pagan prince Oleh the Prophetic is connected to Kyiv topographic realities, contemporary for chronist, in particular, to the toponym «Oleh Tomb», also known from other sources. According to this chronicle Oleh Tomb was placed on the hill Shchekovytsya but the exact localization of the latter is not provided. In the middle of the 19th century Kyiv people called Shchekovytsya the high hill rising over the Podil on the west side. In the works of the later Kyiv scholars this hill was unequivocally identified with Chronicle Shchekovytsya where they localized the grave of Oleh.